Detection of Immune Checkpoint Receptors – A Current Challenge in Clinical Flow Cytometry - Shibru, Benjamin; Fey, Katharina; Fricke, Stephan; Blaudszun, André-René; Fürst, Friederike; Weise, Max; Seiffert, Sabine; Weyh, Maria Katharina; Köhl, Ulrike; Sack, Ulrich; Boldt, Andreas (Frontiers in Immunology, 2021)
Immunological therapy principles are increasingly determining modern medicine. They are used to treat diseases of the immune system, for tumors, but also for infections, neurological diseases, and many others. Most of these therapies base on antibodies, but small molecules, soluble receptors or cells and modified cells are also used. The development of immune checkpoint inhibitors is amazingly fast. T-cell directed antibody therapies against PD-1 or CTLA-4 are already firmly established in the clinic. Further targets are constantly being added and it is becoming increasingly clear that their expression is not only relevant on T cells. Furthermore, we do not yet have any experience with the long-term systemic effects of the treatment. Flow cytometry can be used for diagnosis, monitoring, and detection of side effects. In this review, we focus on checkpoint molecules as target molecules and functional markers of cells of the innate and acquired immune system. However, for most of the interesting and potentially relevant parameters, there are still no test kits suitable for routine use. Here we give an overview of the detection of checkpoint molecules on immune cells in the peripheral blood and show examples of a possible design of antibody panels.